Beyond bars: a path forward from 50 years of mass incarceration in the United States - Budd, Kristen M.; Lane, David Christopher; Muschert, Glenn W.; Smith, Jason A. (SSSP Agendas for Social Justice, 2023)
The year 2023 marks 50 years of mass incarceration in the United States. This timely volume highlights and addresses pressing social problems associated with the U.S.'s heavy reliance on mass imprisonment. In an atmosphere of charged political debate, including tough on crime rhetoric, the editors bring together scholars and experts in the criminal justice field to provide the most up-to-date science on mass incarceration and its ramifications on justice-impacted people and our communities. This book offers practical solutions for advocates, policy and lawmakers, and the wider public for addressing mass incarceration and its effects to create a more just, fair and safer society